Pengaruh Senam Pencak Silat terhadap Kecerdasan Kinestetik Anak Kelompok B TK Aisyiyah Bustanul Athfal Beran Kepil Wonosobo Tahun Ajaran 2015/2016 - Aulia, Eva, Drs. Ilham Sunaryo, M.Pd.AUD (2016)
Purpose the research to knowing effect system of figting gymnastic for children kinesthetic intellegence group B at TK Aisyiyah Bustanul Athfal Beran Kepil Wonosobo academic year 2015/2016. The method using a kind of experimental research with pre-experimental design research design was one group pretest-posttest design. Subjecs the research was children group B at TK Aisyiyah Bustanul Athfal Beran Kepil Wonosobo academic year 2015/2016 amount to 35 children. Data analysis techniques the research used T-test with SPSS 16.0 for Windows. The results of data analysis obtained thitung (-15.244) < -ttabel (-2,032) and signification 0.00 <  (0.05). So that H0 rejected and Ha accepted which means there were significant system of figting gymnastic for children kinesthetic intelligence.